2014
DOI: 10.1111/cmi.12253
|View full text |Cite
|
Sign up to set email alerts
|

TheSalmonella entericagiant adhesin SiiE binds to polarized epithelial cells in a lectin-like manner

Abstract: SummaryThe invasion of polarized epithelial cells by Salmonella enterica requires the cooperative activity of the Salmonella pathogenicity island (SPI) 1-encoded type III secretion system (T3SS) and the SPI4-encoded giant non-fimbrial adhesin SiiE. SiiE is a highly repetitive protein composed of 53 bacterial Ig (BIg) domains and mediates binding to the apical side of polarized epithelial cells. We analysed the binding properties of SiiE and observed lectin-like activity. SiiEdependent cell invasion can be abla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…We found that an adhesive but invasion-deficient strain was randomly distributed on the apical surface. Our previous analysis of the binding specificity of SiiE also did not indicate preferential binding to subpopulations of polarized cells (34). Thus, we exclude heterogeneity in adhesion to polarized cells as a cause of the formation of clusters.…”
Section: Discussionmentioning
confidence: 48%
“…We found that an adhesive but invasion-deficient strain was randomly distributed on the apical surface. Our previous analysis of the binding specificity of SiiE also did not indicate preferential binding to subpopulations of polarized cells (34). Thus, we exclude heterogeneity in adhesion to polarized cells as a cause of the formation of clusters.…”
Section: Discussionmentioning
confidence: 48%
“…Although Ca 2+ ions promote SiiE secretion and folding, we do not assume that they are also directly involved into binding to the target structure. SiiE binds to GlcNAc- and sialic acid-containing structures [5]. Griessl et al .…”
Section: Discussionmentioning
confidence: 99%
“…SiiE, a 595 kDa non-fimbrial adhesin, is the only known substrate for the SPI4-T1SS [4]. SiiE mediates the first intimate contact to the host cell through binding to glycostructures containing N-acetyl-glucosamine and/or α2,3-linked sialic acid [5]. This contact positions the SPI1-T3SS to efficiently translocate effector proteins which lead to actin remodeling and macropinocytosis of the bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Protein structure prediction revealed that these internal repeats may have a structure similar to that of the bacterial immunoglobulin-like domain group 3 (BIg 3) repeats found in another nonfimbrial adhesin of S. enterica, SiiE (57). These immunoglobulin folds mediate protein ligand interactions, which endow SiiE with adhesive properties (65). In addition, these immunoglobulin folds, coupled with Ca 2ϩ binding, could also promote SiiE length extension (57), bringing it into proximity with its cognate receptor on the host cell.…”
Section: Discussionmentioning
confidence: 99%